Ansiedad y desempeño laboral en el personal de enfermería en tiempos de covid 19 en la red de salud cañete - Yauyos, 2021 - Gutiérrez Sánchez, Martha María (2022)
Nursing professionals are regularly exposed to many of the usual stressors of administrative tasks and daily care, for which it has been determined to measure the level of each variable, through the Hamilton Anxiety Scale that refers to manifestations neurovegetative, and the work performance instrument. The dimensions of the Hamilton Anxiety Scale are psychic anxiety, and somatic anxiety, in the levels of absence of anxiety, mild, moderate and severe. The purpose of this research is to find the levels of Anxiety of the nursing staff in times of COVID 19. The approach is quantitative, of an applied type, the non-experimental descriptive, correlational and transectional design. The population was 120 nurses and the sample was 92. The survey is applied using two instruments; A questionnaire on the Hamilton Anxiety Scale and the second on Job Performance will be used, directed with the prior informed consent of the participants.